2013
DOI: 10.1071/rd12037
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal maternal nutrition during early fetal kidney development specifically promotes renal lipid accumulation following juvenile obesity in the offspring

Abstract: Reduced maternal food intake between early-to-mid gestation results in tissue-specific adaptations in the offspring following juvenile-onset obesity that are indicative of insulin resistance. The aim of the present study was to establish the extent to which renal ectopic lipid accumulation, as opposed to other markers of renal stress, such as iron deposition and apoptosis, is enhanced in obese offspring born to mothers nutrient restricted (NR) throughout early fetal kidney development. Pregnant sheep were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…For maternal receiving dietary supplementation with NCG during early pregnancy, the increase in the protein content of the internal organs (heart, liver, kidney, spleen, lung, and peri‐renal BAT of the fetus) may imply that the supply of key nutrients, in particular NCG, is directed towards achieving a high rate of protein accretion and support of visceral organ metabolism and fetal growth. Similarly, previous results demonstrate that maternal nutrition during early pregnancy affects the development of fetus (Ojha et al, 2013), fetal liver (Hyatt et al, 2011), heart (Ojha et al, 2015), and kidney (Fainberg et al, 2013).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For maternal receiving dietary supplementation with NCG during early pregnancy, the increase in the protein content of the internal organs (heart, liver, kidney, spleen, lung, and peri‐renal BAT of the fetus) may imply that the supply of key nutrients, in particular NCG, is directed towards achieving a high rate of protein accretion and support of visceral organ metabolism and fetal growth. Similarly, previous results demonstrate that maternal nutrition during early pregnancy affects the development of fetus (Ojha et al, 2013), fetal liver (Hyatt et al, 2011), heart (Ojha et al, 2015), and kidney (Fainberg et al, 2013).…”
Section: Discussionsupporting
confidence: 62%
“…Abbreviations: NCG, N-carbamylglutamate; OPN, osteopontin; SEM, standard error of the mean. demonstrate that maternal nutrition during early pregnancy affects the development of fetus (Ojha et al, 2013), fetal liver (Hyatt et al, 2011), heart (Ojha et al, 2015), and kidney (Fainberg et al, 2013).…”
Section: Gene Expression Levels In Fetal Peri-renal Batmentioning
confidence: 99%
“…Pregnant sheep with dietary energy restriction exhibit excessive fetal iron deposition in and apoptosis of tubular epithelial cells, as well as excessive fat deposition in kidneys at the early stage of fetal kidney development [27]. Other studies have focused on the lack of dietary protein intake on fetal programming in rodents.…”
Section: Impacts Of Maternal Undernutrition On Metabolic Syndromementioning
confidence: 99%
“…In humans, multiple medical conditions with high serum iron that also trigger iron deposition specifically in the kidney (e.g., sickle cell disease) have significantly higher risk for kidney cancer development (64)(65)(66). Iron deposition specifically to renal epithelium is also induced by hypertension, diabetes, obesity, and chronic kidney disease, all of which are clinical risk factors for RCC (31)(32)(33)(34)(35)(36)(37)(38). In contrast, neither hereditary iron overload (hemochromatosis) nor dietary iron overload induces renal iron deposition nor increases the risk for RCC diagnosis (66).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, we and others have shown that renal epithelium has the highest or among the highest body tissue levels of TfR1 and other master regulatory proteins that increase cellular free iron, underscoring the kidney's unique role in regulating iron and oxygen levels while, perhaps, also predisposing this organ to high iron uptake (28)(29)(30). The tendency of renal epithelium for iron uptake is evidenced by demonstration that various conditions associated with RCC (hypertension, obesity, diabetes, chronic kidney disease, and hypoxia) each trigger body iron to mobilize and accumulate specifically in the kidney (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%